Pengaruh Cashback Dan Gratis Ongkir Terhadap Impulse Buying Melalui Brand Image Produk Parfum HMNS Pada Platform Shopee - Nasywa Chintami Rahmadani Putri; Dewi Sri Woelandari; Ferawaty Puspitorini (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to analyze the influence of cashback and free shipping on impulse buying through brand image of HMNS perfume products on the Shopee platform. This research employed a quantitative approach with an explanatory research design. The population of this study consisted of Generation Z consumers residing in Narogong Indah Housing Estate, Bekasi. A total of 120 respondents were selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results indicate that free shipping has a positive and significant effect on impulse buying, while cashback does not have a significant effect on impulse buying. In addition, brand image has a positive and significant effect on impulse buying and serves as a mediating variable in the relationship between cashback and free shipping on impulse buying. These findings suggest that free shipping is more effective than cashback in encouraging impulse purchases, particularly when supported by a strong brand image. The study is expected to provide valuable insights for companies in developing promotional strategies and strengthening brand image to enhance consumers' impulse buying behavior.